Study of role of Magnesium sulfate in prevention of eclampsia - Gadappa, Srinivas N.; Dixit, Pratibha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hypertensive disorders of pregnancy have a clinical spectrum ranging from non-severe to severe preeclampsia and then potentially to eclampsia. Magnesium sulfate is drug of choice for women with eclampsia and now adapted for prophylaxis of seizures in women with preeclampsia. Methods: It is randomized clinical trial, including 876 patients with preeclampsia fulfilling inclusion criteria. Patients with severe preeclampsia received anticonvulsant prophylaxis with magnesium sulfate. Patients with non-severe preeclampsia were randomized in two groups study group and control group. Patients in study group had received anticonvulsant prophylaxis with magnesium sulfate. The data obtained was analyzed with respect to maternal and perinatal outcome, severity of disease progression and adverse reactions of magnesium sulphate in each group. Results: In this study statistically, significant difference was seen with respect to severity of disease progression and incidence of eclampsia among study and control group. Conclusions: Administration of Magnesium sulfate in patients with non-severe preeclampsia does not affect the progress of labour or perinatal outcome, on contrary it improves maternal outcome by reducing incidence of eclampsia and progression of disease, without significant side effect of drug.